2014
DOI: 10.1016/j.healthplace.2013.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Measuring community integration using Geographic Information Systems (GIS) and participatory mapping for people who were once homeless

Abstract: Measures of community integration rely on self-report assessments that often quantify physical or social participation, but fail to capture the individual׳s spatial presence in the community. The current study documents the activity space, or area of daily experiences, of 37 individuals who were once homeless through participatory mapping and Geographic Information Systems (GIS). Contrary to expectations, there was no significant relationship between activity space size and community integration measures, exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…These stationary periods are determined by applying a convex hull detection algorithm to the raw GPS data. Convex hull methods have been used recently in several community detection and activity space projects (Chan, Helfrich, Hursh, Sally Rogers, & Gopal, ; Yin et al., ). This algorithm iteratively creates a minimum bounding polygon, or the smallest convex subset of the real plane containing the set of coordinates.…”
Section: Methodsmentioning
confidence: 99%
“…These stationary periods are determined by applying a convex hull detection algorithm to the raw GPS data. Convex hull methods have been used recently in several community detection and activity space projects (Chan, Helfrich, Hursh, Sally Rogers, & Gopal, ; Yin et al., ). This algorithm iteratively creates a minimum bounding polygon, or the smallest convex subset of the real plane containing the set of coordinates.…”
Section: Methodsmentioning
confidence: 99%
“…Using a cognitive mapping process (Chan et al, 2014), we utilised sketch maps drawn by respondents during the focus groups to determine grazing areas and the spatial extent and patterns of seasonal livestock mobility before and after fences. Participatory mapping can form an important aspect of generating local spatial knowledge (Chapin et al, 2005, Neitschman, 1995, since it allows resource users to convey not only positions of activities but also background details concerning the locations and drivers of land use activities (Levine and Feinholz, 2015).…”
Section: Participatory Mapping and Pgismentioning
confidence: 99%
“…[16][17][18][19] While this approach provides a strong indication of the direction of a person's activities within their proximal community, outlier activity points can lead to an overestimation of the size of activity space. [20][21][22][23][24] To address this problem, the current study used a mean circle approach. 17,19 The mean circle method represents one of the earlier attempts to define areas of importance based on the presence of point or line phenomena.…”
Section: Participatory Social Mappingmentioning
confidence: 99%
“…In their 2012 study, Boscoe et al 23 observed a close correlation (r 2 > 0.9) in comparing Euclidean and network distances for travel times between community hospitals and sample point locations. Chan et al 24 have compounded on the earlier work of Boscoe et al 23 in the use of Euclidean distance measures in finding proximities of study participants' homes to community features. Last, an outlier analysis was conducted to identify activity points that did not fall within a participant's normal activity space.…”
Section: Participatory Social Mappingmentioning
confidence: 99%